Evaluation of water stress in strawberry crops under a humid climate - Pérez-Marroquín Guillermo Jesuita; Platas-Galindo, Edgar; Cruz-Pérez, José Clemente; Berdeja-Arbeu, Raúl; Enríquez-García, Fabián; Zaldívar-Martínez, Pablo (Revista Mexicana de Ciencias Agrícolas, 2026)
Strawberries (Fragaria x ananassa Duch.) are a crop of high commercial value whose productivity depends on efficient irrigation management, given their sensitivity to water deficits. In humid regions, high relative humidity reduces evaporative demand and limits the effectiveness of indicators based on leaf temperature, such as the crop water stress index (CWSI). This research aimed to evaluate the usefulness of the crop water stress index as a criterion for managing strawberry irrigation under humid climate conditions. The study was conducted in 2022 in a greenhouse of the Faculty of Agricultural and Livestock Sciences of the Meritorious Autonomous University of Puebla, Teziutlán, Puebla. Four irrigation treatments (100, 90, 80 and 70% of reference evapotranspiration, ETc) were established in a completely randomized design with four replications. Morphological and quality variables (number of flowers, number of fruits, polar and equatorial diameters, and total soluble solids) were recorded, and the crop water stress index was monitored throughout the cycle. The results showed that 80% ETc treatment maintained a yield similar to that of the 100% treatment, indicating potential water savings without affecting production. However, fruits with full irrigation reached a higher content of total soluble solids, whereas deficit treatments generated larger fruits but with lower sweetness, reflecting a trade-off between yield and quality. The crop water stress index registered low (0.3-0.55) and homogeneous values across treatments, confirming that, in humid climates, it is not a single reliable indicator and must be complemented with other physiological and productive variables.